Financial development in times of economic crisis- case study Latin America: Argentina, Chile and Colombia - Amado - Piñeros, Martha Isabel (Universidad Francisco de Paula Santander, 2020)
The regions that are part of a geographical sector must postulate scenarios of autochthonous protagonism among their leaders and change managers, not only from the local but also from the financial point of view, in order to consolidate long-term financial developments. Colombia, Chile and Argentina are emerging as examples of crises over several decades and their economies and financial developments have been conditioned to these historical moments. The objective of this article was to address the main measures and indicators that the governments of Colombia, Argentina and Chile have postulated regarding the management of finances. The methodological process was documentary, taking reports from ECLAC, the World Bank, OECD and also internal levels to each commented region. The economy reports, growth studies will be the primary source of review. Among the results obtained is the presentation of sectoral analyzes and ideas rescued from said cooperation organizations between Colombia, Argentina and Chile as pillars of the local and regional economy. It seeks to serve as a base for future accounting professionals in the historical environment so that globalized scenarios of the Latin American region are fully understood.